Measuring antecedents of customer satisfaction: an empirical analysis of telecom services in Pakistan - Rind, M. M.; Qureshi, I. A.; Saand, A. S.; Memon, S.; Shah , Asadullah (University of Sindh Jamshoro, Pakistan, 2016)
Organization's profitability is directly proportional to customer satisfaction. Sustainable competitive advantage can only be attained through services excellence and quality products. The effects of the antecedents of service quality on customer satisfaction has been under discussion among researchers since long. The primary aim of this study is to investigate the antecedent of customer satisfaction in the telecommunications industry of Pakistan. Primary data has been gathered from telecom services, walk in customers at various telecom service providers services centers. In an effort to measure whether users of telecom services are satisfied with services offered by various telecom operators in Pakistan, the proposed model was tested on the basis of responses received from 236 users. Data was collected from major cities of Pakistan, i. e. Islamabad, Karachi and Lahore through random distribution of structured questionnaire. Obtained data was analyzed using structural equation modelling analysis techniques. Reliability and validity of measurement model was examined by performing confirmatory factor analysis. Results show that perceived quality, perceived value and customer expectations has positive and significant impact on customer satisfaction. However, customer expectation was found to be the best predictor of customer satisfaction in telecom services sector of Pakistan.